2017
DOI: 10.1108/et-11-2016-0169
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological research study on writer’s block: causes, processes, and results

Abstract: Purpose The purpose of this paper is to investigate the causes, processes of writer’s block experienced by a group of classroom teacher candidates and its impact on them. Design/methodology/approach The phenomenological design, which is a qualitative research design, was preferred in the research since it was aimed to investigate the causes, processes of writer’s block experienced by a group of classroom teacher candidates and its effects on the students. Findings As a result of the data analysis, it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Zorbaz's (2015) study revealed that socio-economic status and writing in L1 and L2 do not impact writer's block, yet the low frequency of reading and writing along with inadequate writing practices, lead to writer's block in higher education. In addition, Baştuğ et al's (2017) phenomenological study also revealed that text types, inappropriate and unclear task instructions, and the limited time allocated to students appeared as reasons for blocks.…”
Section: Writer's Blockmentioning
confidence: 97%
See 2 more Smart Citations
“…Zorbaz's (2015) study revealed that socio-economic status and writing in L1 and L2 do not impact writer's block, yet the low frequency of reading and writing along with inadequate writing practices, lead to writer's block in higher education. In addition, Baştuğ et al's (2017) phenomenological study also revealed that text types, inappropriate and unclear task instructions, and the limited time allocated to students appeared as reasons for blocks.…”
Section: Writer's Blockmentioning
confidence: 97%
“…Such stoppage in the writing process may bring about temporary but significant decreases in the quality and quantity of written works. Therefore, it is often accompanied by stress, a sense of failure, and hopelessness, culminating with abandoning writing, tearing and throwing away the whole text, or permanently calling off the project (Baştuğ et al, 2017). Writers often report that blockage manifests itself while generating, articulating, and expressing ideas and choosing which to follow (Ahmed & Güss, 2022).…”
Section: Writer's Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Procrastination is defined as the postponing of or failure to begin tasks such as preparing for exams and completing assignments (Milgram, Mey-Tal & Levinson, 1998;Solomon & Rothblum, 1984). In particular, producing texts for assessment causes student blocks, procrastination, and perfectionism (Bastug, Ertem, & Keskin, 2017;Flett, Stainton, Hewitt, Sherry, & Lay, 2012;Grunschel, Patrzek, & Fries, 2013;Lonka et al, 2014). Research shows that students whose language of instruction is their second language experience a higher level of procrastination in their first year of study than do native speakers (Sarid, Peled, & Vaknin-Nusbaum, 2021).…”
Section: University Students' Writing Conceptionsmentioning
confidence: 99%
“…Castillo (2014) suggested that most writers (even longpracticed writers) experience this in one way or another. Bastug et al (2017) noted that writer's block is related to certain cognitive and affective issues in the writing process. These issues intensify when writing doctoral dissertations, particularly in the literature review (Rose & Rose, 2009).…”
Section: Write Smallmentioning
confidence: 99%